On the Evangelical Mind and Consulting the Faithful - Green, Jay (Christian scholar's review, 2018)
As we near the twenty-fifth anniversary of Mark Noll’s The Scandal of the Evangelical Mind, those who wish to make sense of its legacy confront a rather curious puzzle. If the book aimed to energize a generation of evangelicals to establish themselves in elite universities, to produce credible, meaningful scholarship, and to leave a record of thoughtful reflection on modern culture, then mission accomplished! However, if its goals extended to revitalizing the culture of thought among ordinary evangelicals, its legacy is much less clear; especially in light of the public witness of American evangelicals in the age of Donald Trump. As someone who has enjoyed the fruits of a post-Scandal evangelical intellectual renaissance since 1994, I am perplexed and troubled by its seeming lack of penetration among “folks in the pew.” This seeming paradox has led me to reflect anew on features of my own story.